Introduction to the economics of financial markets - Bradfield, James (Oxford University Press, 2007)
"There are many textbooks for business students that provide a systematic, introductory development of the economics of financial markets. However, there are as yet no introductory textbooks aimed at more easily daunted undergraduate liberal arts students. Introduction to the Economics of Financial Markets fills this gap by providing an extremely accessible introductory exposition of how economists analyze both how, and how well, financial markets organize the intertemporal allocation of scarce resources. The central theme is that the function of a system of financial markets is to enable consumers, investors, and managers of firms to effect mutually beneficial intertemporal exchanges. James Bradfield uses the standard concept of economic efficiency (Pareto Optimality) to assess the efficacy of the financial markets. He presents an intuitive, and introductory, understanding of the primary theoretical and empirical models that economists use to analyze financial markets, and then uses these models to discuss implications for public policy. Students who use this text will acquire an understanding of the economics of financial markets that will enable them to read, with some sophistication, articles in the public press about financial markets and about public policy toward those markets. The book is addressed to undergraduate students in the liberal arts, but will also be useful for undergraduate and beginning graduate students in programs of business administration who want an understanding of how economists assess financial markets against the criteria of allocative and informational efficiency."--Provided by publisher.